One-Pot Synthesis of Ortho-Halogen-Substituted Aryl(Alkynyl)Phosphinates Via Aryne-Phosphite-Haloalkyne Coupling - CHoi, Eun Gyeong; Ji, Suhyun; Lee, Duck-Hyung; Han, Seojung (John Wiley & Sons Ltd., 2025)
The one-pot formation of two C？P bonds and one C？halogen bond was achieved through a mild three-component coupling reaction utilizing arynes, phosphites, and haloalkynes. In this reaction, the aryl anion, generated from the nucleophilic addition of phosphite to aryne, directly attacked the halogen of the haloalkyne. The reaction proceeded smoothly with a wide substrate scope and good functional group tolerance. This operationally simple method enables direct access to ortho-halogen-substituted aryl(alkynyl)phosphinates. The synthetic utility of ortho-halogen-substituted aryl(alkynyl)phosphinates with prospective applications in natural product synthesis, medicinal chemistry, and materials chemistry has also been demonstrated.